Uremia accelerates both atherosclerosis and arterial calcification in apolipoprotein E knockout mice - Massy, Ziad A; Ivanovski, Ognen; Nguyen-Khoa, Thao; Angulo, Jesus; Szumilak, Dorota; Mothu, Nadya; Phan, Olivier; Daudon, Michel; Lacour, Bernard; Drüeke, Tilman B; Muntzel, Martin S (American Society of Nephrology, 2005)
Chronic renal failure (CRF) favors the development of atherosclerosis and excessive calcification of atheromatous lesions. CRF was induced in apolipoprotein E knockout (apoE(-/-)) mice to study (1) a possible acceleration of aortic atherosclerosis, (2) the degree and type of vascular calcification, and (3) factors involved in the calcification process. For creating CRF, 8-wk-old apolipoprotein E gene knockout (apoE(-/-)) mice underwent partial kidney ablation. Control animals underwent sham operation. Aortic atherosclerotic plaques and calcification were evaluated using quantitative morphologic image processing. At 6 wk after nephrectomy, CRF mice had significantly higher serum urea, cholesterol, and triglyceride concentrations than non-CRF controls. The serum levels of advanced oxidation protein products were elevated in the uremic group and were correlated with serum urea levels. Atherosclerotic lesions in thoracic aorta were significantly larger in uremic apoE(-/-) mice than in nonuremic controls. The relative proportion of calcified area to total surface area of both atherosclerotic lesions and lesion-free vascular tissue was increased in aortic root of uremic apoE(-/-) mice when compared with controls. The calcium deposits were made of hydroxyapatite and calcite crystals. In addition, plaques from uremic animals showed a significant increase in collagen content, whereas the degree of macrophage infiltration was comparable in both groups. There was no difference in mean arterial BP. These findings demonstrate that CRF aggravates atherosclerosis in apoE(-/-) mice. Moreover, CRF enhances arterial calcification at both atheromatous intimal sites and atheroma-free medial sites. We anticipate that this experimental model will be useful to test treatment strategies aimed at decreasing the accelerated atherosclerosis and arterial calcification in uremia.